DETERMINANTS FACTOR OF DIGITAL ZAKAT PAYMENT BY INDONESIAN MUZAKKI - Rahayuningsih, Tanti Eisyah; Susilowati, Dewi; Sudibyo, Yudha Aryo (Islamic Economic Scholar Association and Faculty of Economics and Business Universitas Jenderal Soedirman, 2021)
Collecting zakat using a digital platform is an innovation carried out by amil zakat institutions which are expected to be able to increase zakat collection. Even so, from year to year there is still a gap between the potential of zakat and the realization of zakat. So this study aims to determine the effect of performance expectancy, effort expectancy, social influence, education and trust on muzakki's intention in paying zakat using a digital platform. The population in this study is the Indonesian Muslim community. The sample of this study is 107 people samples are sampling selection using purposive sampling method with the criteria the Indonesian Muslim community who had experienced paid zakat using a digital platform. The results of this study indicate that: (1) Performance expectancy positively affect the muzakki intention in paying zakat using a digital platform; (2) Effort expectancy does not affect the muzakki intention in paying zakat using a digital platform; (3) Social influence does not affect the muzakki intention in paying zakat using a digital platform; (4) Trust positively affect the muzakki intention in paying zakat using a digital platform; (5) Education does not affect the muzakki intention in paying zakat using a digital platform.